A Comparative Approach to the Dream-city: Mario Levrero and Mircea C?rt?rescu - Diz Villanueva, Alba (2020)
Despite the stylistic and thematic differences between them, Mario Levrero and Mircea C?rt?rescu give a main role to dreams and onirism in their narrative texts. This fact has consequences for the fictional space inasmuch as it results in an urban cultural model (dream-city). This paper analyses Levrero’s Trilogía involuntaria and Mircea C?rt?rescu’s Orbitor in order to examine the specific characteristics of that model, the main differences and concomitances.